Enthesitis and its relationship with disease activity, functional status, and quality of life in psoriatic arthritis: a multi-center study - DURUÖZ, MEHMET TUNCAY; ACER KASMAN, SEVTAP (SPRINGER HEIDELBERG, 2020)
Psoriatic arthritis (PsA) is an inflammatory arthritis with distinct phenotypic subtypes. Enthesitis is assigned as a hallmark of the disease, given its significant relations to disease activity and quality of life. Our objective is to evaluate the prevalence of enthesitis and its association with some clinical parameters, particularly quality of life, using data from a national registry. Patients with PsA meeting ClASsification criteria for Psoriatic Arthritis (CASPAR) were enrolled by means of a multi-centre Turkish League Against Rheumatism (TLAR) Network Project. The following information was recorded in web-based case report forms: demographic, clinical and radiographic data; physical examination findings, including tender and swollen joint counts (TJC and SJC); nail and skin involvement; Disease Activity Score-28 for Rheumatoid Arthritis with Erythrocyte Sedimentation Rate (DAS 28-ESR); Bath Ankylosing Spondylitis Disease Activity Index (BASDAI); Maastricht Ankylosing Spondylitis Enthesitis Score (MASES); Psoriasis Area Severity Index (PASI); Bath Ankylosing Spondylitis Radiology Index for the spine (BASRI-s); Health Assessment Questionnaire (HAQ); Bath Ankylosing Spondylitis Functional Index (BASFI); Health Assessment Questionnaire for the spondyloarthropathies (HAQ-s); Psoriatic arthritis quality of Life scale (PsAQoL); Short Form 36 (SF-36); Hospital Anxiety Depression Scale (HADS); Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-F); and Fibromyalgia Rapid Screening Tool (FiRST) scores. The patients were divided into two groups, namely with and without enthesitis, based on the triple Likert-type physician-reported statement of 'active enthesitis', 'history of enthesitis' or 'none' in the case report forms. Patients with active enthesitis were compared to others in terms of these clinical parameters. A total of 1130 patients were enrolled in this observational study. Of these patients, 251 (22.2%) had active enthesitis according to the clinical assessment. TJC, HAQ-s, BASDAI, FiRST and PsAQoL were significantly higher whereas the SF-36 scores were lower in patients with enthesitis (p < 0.05). Chronic back pain, dactylitis, and tenosynovitis were more frequent in the enthesopathy group (59.4%/39%, 13.1%/6.5% and 24.7%/3.4%, respectively). Significant positive correlations between the MASES score and the TJC, HAQ, DAS 28-ESR, BASDAI, FiRST and PsAQoL scores, and a negative correlation with the SF-36 score were found. When linear regression analysis was performed, the SF-36 MCS and PCS scores decreased by - 9.740 and - 11.795 units, and the FiRST scores increased by 1.223 units in patients with enthesitis. Enthesitis is an important involvement of PsA with significant relations to quality of life determined with PsAQoL and SF-36 scores. Our study found higher frequency of dactylitis and chronic back pain, and worse quality of life determined with SF-36 and PsAQoL scores in patients with enthesitis.
Keywords: Enthesitis; Psoriatic arthritis; Enthesopathy; Registry; Disease activity; Quality of life; HEALTH-ASSESSMENT QUESTIONNAIRE; ANKYLOSING-SPONDYLITIS; CLINICAL CHARACTERISTICS; CLASSIFICATION; DACTYLITIS; CRITERIA; FIBROMYALGIA; PREVALENCE; COHORT; SPONDYLARTHROPATHY